Um processo dirigido a modelos para geração de código - Papotti, Paulo Eduardo (2013)
Software development is an activity in constant change over time. Given the complexity and high cost that exists in software construction, there is high demand, especially in the software industries, for methodologies and tools that enable to increase software productivity by spending less time and effort in its development. Among the challenges that exist in Software Engineering, there is a need in knowing and exploring techniques and tools that enable to increase productivity and maintai software quality. Approaches related to model-driven development can be used as a starting point for modeling and to specify the requirements of a software system. Models provide a representation with higher level of abstraction of system design and assist to understand the system. Through the execution of model-to-code transformation mechanisms, implementation artifacts for different technologies can be generated based on data extracted and interpreted from models. Furthermore, reflexive metaprogramming is a technique that can be used to complement the code generation performed by model-to-code transformations, automating most of tasks of developers, such as CRUD (Create, Retrieve, Update, Delete) functionalities, freeing them to perform more important tasks in development process. Therefore, this research proposes a software process to guide professionals in developing applications using such techniques to accomplish code generation, in order to increase software productivity and facilitate maintenance.